Applied management in vocational education reform in Serbia - Jovčić Ljiljana (Association of Nurses Technicians and Midwives, 2018)
In the reforming of modern education system, its basic functions can be used as main points, consisted in the following; enabling of each young man, as well as adults, for the social practice, for the social labor division inclusion and social life and a contribution of more complete human personality expression. In that manner, the economic, social and human function of education are included. It enjoins the realization of the main aims of education and breeding: to create a polite person, productive worker, to enable everyone to find their place in a social community and to become active and useful member of a society where he lives. That concept of a system of education covers all the fields, levels and forms of institutional and non-institutional education. One of the main characteristics of the system will be: ﬂexibility and adaptability, the possibility of a quick and efficient adaptation to new social needs and expectations in concordance with science- technological development demands. The work compares the vocational education in Serbia to the same level in the European Union and other European countries, then it highlights the necessity of reforms. It implies the importance of the use of management demands as social technology which enables the efficiency achievement and the eﬀectiveness of institutions and ventures.